Study and Analysis The Effect of Camera Calibration Methods on Quality of Stereo Images Rectification - خليل بتول; السموءل صالح (Latakia University Journal -Engineering Sciences Series, 2023)
Stereo calibration and rectification are considered to be one of the most important pre‐steps in computer vision, virtual reality and 3D reconstruction applications. Fisheye lenses, which has a large Field of View, have been receiving increasing attentions in recent years. But these lenses add a high amount of distortion to the images. Calibration is also a must when rectifying stereo image pairs. Rectification makes the correspondence done only along the x-axis of the rectified images. Because only few researches compared calibration algorithms and their impact on stereo image rectification. This paper presents a study and analysis of two state of the art calibration algorithms which are Scaramuzza algorithm which suggests a generic camera model to calibrate all kinds of cameras. And Bouguet algorithm that is based on Bouguet’s work on calibration for pinhole camera model with the addition of some changes in distortions modeling. The performance evaluation of the algorithms have been done based on subjective measures using GIMP program. While the objective performance evaluation was done by studding mean square rectification error parameter (MSRE). The results showed that Bouguet algorithm is more accurate and flexible, as it gave better results in stereo image rectification.